O37 Speedboat colorectal submucosal dissection; preliminary analysis of polyp surface and fibrosis with the procedural time. (19th June 2022) - Zeidan, Shady; Elkady, Soad; Gatopoulos, Polychronis; Muller, Andrew; Gonidis, Lazaros; Mangam, Sudhakar; Bagla, Nipin; Sebastian, Joseph; Tsiamoulos, Zacharias
Abstract : Introduction: The 'Speedboat-RS2/SRS2' (Creo-Medical/Wales/UK) is the first multi-modality device, incorporating bipolar-radiofrequency/BRF energy cutting, microwave energy coagulation/MWC, an integrated needle for submucosal injection and a rotatable blade with a heat insulated hull for protection. Methods: A prospective database of colorectal endoscopic submucosal dissection/ESD cases using SRS2 device was initiated from June 2018 to Dec 2021. One experienced operator performed all cases. Short and long-term clinical outcomes were recorded. Linear regression was used to explore whether factors, such as polyp size/surface/location/morphology could implicate with the duration of the procedure in minutes. Results: 123 patients were subject to ESD using submucosal tunneling technique. 17abandoned (9 for muscle retraction sign, 7 advanced cancer), 4 for medical emergencies and 4 for device failures. Out of 106, endoscopically complete en-bloc resection was achieved in 93.3% (n=99), curative rate 87% (n=86). Conversion to piecemeal resection 6.7% (n=7) due to inappropriate booking and scope difficulties. Within the en-bloc group, mean polyp 5.15cm ± 2.85 SD, mean polyp surface 19.23cm 2 ± 20.72 SD. Non-rectal polyps 50/99 (50%), non-granular polyps 34/99 (34%), high dysplastic polyps 27/99 (27%) 13/99 (31%). Eight T1 cancers with <1000μm depth of invasion and no adverse histology features had no recurrence in endoscopy (7/8) or surgery (1/8). 3 T1 cancers with adverse histology features had not recurrence on endoscopy (1/3) and no residual malignancy in surgical specimen (2/3). First surveillance endoscopy available to 51/99 (50%) with no recurrence identified. MWC used to pre-coagulate and control bleeding in all cases. Hemostatic monopolar forceps was required in 9/99 cases. Endoscopically controlled delayed bleeding occurred in 2 patients (2%). No perforation was recorded. Overall mean procedural time in minutes was 96.36 ± 74.18 SD. Regression analysis revealed significant effect of cm2 size and fibrosis on the duration of the procedure ( p < . 001, R 2 = .866), indicating an increase of 3.25 minutes per 1cm2 of increase in polyp surface and an increase of 7.47 minutes when severe fibrosis is encountered; with a baseline time of 28 mins reflecting polyp of 0cm. Conclusions: These first results demonstrate that Speedboat is an effective and safe device for submucosal colorectal dissections. SRS2 performed in a timely manner, and the preliminary correlation of the time of the procedure affected by polyp surface and degree of fibrosis warrants further analysis.